‘AM AND KHAṢ LINGUISTIC METHOD CONCEPT AND IMPLEMENTATION IN ISLAMIC LAW DETERMINATION - Muchtar, Abdul Haris; Maulidizen, Ahmad; Safaah, Amriatus (Sekolah Tinggi Ilmu Syariah Husnul Khotimah, 2022)
Al-Quran is a way of life for Muslims. Therefore, the Koran is essential to learn because it is a source of Islamic law (maṣādir al-aḥkām) in solving a problem. The method of issuing a rule from the Quran is called ijtihad. The mujtahid tasks must be to understand the text (nash), understand the meaning of a pronunciation, region, object, designate the word for the word, and the type and degree of its action. Ushul Fiqh Expert divides into two parts, namely the appointment (dilālah) of the text for meaning and the appointment (dilālah) of the text of the syaraʻ law directly. The position (dilālah) of the purpose text includes the discussion of ʻam and khas. Therefore, this article will explain how to use the legal norms and language rules in the science of ushul fiqh, one of the definitions of ʻam and khas and implementation in determining Islamic law. The explanation includes the rules of language lughāwiyah, ʻam and khaṣ and ​​the law uses theorem ʻam. This article will analyze and explore how the actual science of Ushul fiqh is used and the arguments about the istihbat law itself. the rules of language and other things to know how the idea is used based on the correct rules.